200th anniversary (1804-2004) of the publication of the poem: Vaccinatio ; De Jenneriano invento optime merito ; Carmen elegiacum ; by Croatian scientist Luko Stulli - Borovečki, Ana (Array, 2004)
Luko Stulli (1772-1828) was physician who in 1800 performed the first vaccination in Dubrovnik. He was one of the last Latin poets in the Croatian literature. In 1804, Stulli wrote the poem Vaccinatio ; De Jenneriano invento optime merito ; Carmen elegiacum ( Vaccinatio) ; On teh Outstanding Jennerian Inevntion ; Elegiac Poem). Thus, the vaccination effort in Durbovnik has ahistorical and literary significance. This paper presents a critical reading of the poem Vaccinatio by Luko Stulli, together with important medical historical and literary background relevant to it. The complete, original Latin poem and its English and Croatian translation are found in the appendix of the article (p. 661).